Empowerment of PKK members for reducing stunting in the Tasikmalaya City - Lopuhaa, Hesty Marsya; Ginting, Arwanto Harimas (Goodwood Publishing, 2024)
PKK members to optimize activities and programs related to stunting, which is in line with one of the goals of sustainable development (SDGS) in the world, called creating a healthy and prosperous life. Research Methodology: Data were collected through a literature review and consultation with village officials and community groups participating in empowerment. Data reduction was performed, and the results of the analysis were explained and clarified with descriptive descriptions. Results: This study reveals that PKK members, in this case, are partners with the Tasikmalaya city government, who have been empowered with several programs to accelerate stunting reduction, but the results of implementation from society have not been maximized. Limitations: This study also specifically examines women's empowerment in Mugarsari Village, Tamansari District, Tasikmalaya City, which has a high prevalence of stunting. Contributions: This study contributes to the field of healthy living and the welfare of the Indonesian people in handling stunting, starting from the smallest scope, surrounding community organizations. The findings and recommendations are relevant to policymakers, city governments, and researchers of local governance and community empowerment.